Mannen tegen seksueel geweld. (Amsterdam : Stichting Mannen tegen seksueel geweld, 1985)
Fonds Suzan Daniel (FSD)
Periodiciteit: driemaandelijks
Redactie: PB 11597, 1001 GN Amsterdam
Nederlands
Periodiek